Assessing Tarnobrzeg Cardiology Clinic patients’ level of knowledge of coronary heart disease risk factors. - Gronek, Anna; Hada, Monika; Mrozek, Marta (Journal of Education, Health and Sport, 2018)
The aim of this paper is to present the level of knowledge of Tarnobrzeg Cardiology Clinic patients of the risk factors of coronary heart disease. The data required to support the paper’s statement was collected from 100 patients. Diagnostic survey was used as the method. A questionnaire with a set of 22 questions was used as the research tool.The obtained results show that the level of knowledge is not satisfactory and the patients require further education. It was found that gender is not a factor differentiating the level of knowledge. However, urban residents are better informed than rural residents. It was concluded that the older the patient is the lower level of knowledge of coronary heart disease risk factors he or she possesses. Also, patients with higher education are more knowledgeable.The research presented in the paper indicates there is an increased need of educating the population on coronary heart disease risk factors, promoting cardiovascular diseases prevention and engaging the medical community in spreading the knowledge.